2021
DOI: 10.1108/reps-02-2020-0020
|View full text |Cite
|
Sign up to set email alerts
|

Assessing fiscal sustainability in Egypt: a comparative study

Abstract: PurposeThis paper aims to assess the fiscal sustainability in Egypt during the period 1990–2018 using deficit accounts (DA) approach. It also tries to investigate the possibility of applying generational accounts (GA) in Egypt as a new approach to assess fiscal sustainability.Design/methodology/approachThis paper tries to assess fiscal sustainability in Egypt during 1990–2018 using DA and GA approaches. DA approach includes primary deficit indicator, tax gap indicator, augmented Dickey-Fuller stationarity test… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(6 citation statements)
references
References 36 publications
0
6
0
Order By: Relevance
“…Results in tables (4-5), (4)(5)(6), and (4-7) confirm that there is no serial correlation in residuals, there is homoscedasticity in the two models, and the coefficients are stable over time. The results of the normality test in tables (4)(5) and (4)(5)(6) prove that residuals follow the normal distribution. While in table (4)(5)(6)(7) the results show that residuals don't follow the normal distribution.…”
Section: Domestic Debt Effectmentioning
confidence: 76%
See 3 more Smart Citations
“…Results in tables (4-5), (4)(5)(6), and (4-7) confirm that there is no serial correlation in residuals, there is homoscedasticity in the two models, and the coefficients are stable over time. The results of the normality test in tables (4)(5) and (4)(5)(6) prove that residuals follow the normal distribution. While in table (4)(5)(6)(7) the results show that residuals don't follow the normal distribution.…”
Section: Domestic Debt Effectmentioning
confidence: 76%
“…The results of the normality test in tables (4)(5) and (4)(5)(6) prove that residuals follow the normal distribution. While in table (4)(5)(6)(7) the results show that residuals don't follow the normal distribution.…”
Section: Domestic Debt Effectmentioning
confidence: 84%
See 2 more Smart Citations
“…This supports the view that Egypt's fiscal policy is sustainable, consistent with previous studies. For instance, Al Sayed et al (2021) used a cointegration analysis to show that the fiscal policy in Egypt was sustainable from 1990/ 1991 to 2017/2018. Similarly, Abdullah et al (2012) found a cointegration between fiscal sustainability indicators and GDP in Malaysia, indicating fiscal sustainability.…”
Section: Discussionmentioning
confidence: 99%